Ultrastructural and Molecular Changes in the Developing Small Intestine of the Toad Bufo regularis - S. A. Sakr; G. M. Badawy; H. T. El-Borm (The Scientific World Journal)
The ontogenetic development of the small intestine of the toad Bufo regularis was investigated using twofold approaches, namely, ultrastructural and molecular. The former has been done using transmission electron microscope and utilizing the developmental stages 42, 50, 55, 60, 63, and 66. The most prominent ultrastructural changes were recorded at stage 60 and were more evident at stage 63. These included the appearance of apoptotic bodies/nuclei within the larval epithelium, the presence of macrophages, swollen mitochondria, distorted rough endoplasmic reticulum, chromatin condensation, and irregular nuclear envelop, and the presence of large vacuoles and lysosomes. The molecular investigation involved examining DNA content and fragmentation. The results showed that the DNA content decreased significantly during the metamorphic stages 60 and 63 compared with both larval (50 and 55) and postmetamorphic (66) stages. The metamorphic stages (60 and 63) displayed extensive DNA laddering compared with stages 50, 55, and 66. The percentage of DNA damage was 0.00%, 12.91%, 57.26%, 45.48%, and 4.43% for the developmental stages 50, 55, 60, 63, and 66, respectively. In conclusion, the recorded remodeling of the small intestine represents a model for clarifying the mechanism whereby cell death and proliferation are controlled.